Inverted abdominoplasty as a reconstructive option in a patient with lipolaser burn sequelae - González, Yazmin G.; Anda, Roberto De; Soriano, Kimberly G. (International Journal of Research in Medical Sciences, 2025)
Burn sequelae secondary to lipolaser procedures pose a therapeutic challenge in plastic surgery due to both aesthetic and functional alterations of the abdominal tissue. We present the case of a 48-year-old female patient with an epigastric burn following lipolaser, resulting in cutaneous deformity, retraction, and pathological scarring. She was successfully treated with an inverted abdominoplasty combined with a lower mini-abdominoplasty. This approach enabled the resection of damaged tissue, redistribution of upper abdominal skin, and improvement of the abdominal contour. The surgical procedure was performed under general anesthesia, lasting 150 minutes, with hospital discharge at 24 hours. Although a new scar was created in the upper abdomen, it was well concealed within the natural inframammary folds. During follow-up, a late complication of keloid scarring was identified and effectively managed with three intralesional triamcinolone injections, without the need for further surgical intervention. Postoperative evolution was satisfactory, achieving both functional recovery and favorable aesthetic outcomes, with improved quality of life and body image perception. This case demonstrates that inverted abdominoplasty is an effective reconstructive option for patients with upper abdominal deformities resulting from inadequately performed aesthetic procedures. When properly indicated, carefully planned, and technically well executed, this technique offers safe and predictable results in the context of burn sequelae, and continues to consolidate its role as a valuable tool within the reconstructive surgical arsenal.